Impacts of Nearshore Wave‐Current Interaction on Transport and Mixing of Small‐Scale Buoyant Plumes - Angelica R. Rodriguez; Sarah N. Giddings; Nirnimesh Kumar (Geophysical Research Letters)
Abstract Small‐scale buoyant outflows have the potential to impact beach contamination, nutrient exchange, productivity, larval recruitment, and carbon chemistry in the nearshore region where surface gravity waves influence momentum and energy transport. This study aims to understand the dynamics leading to the fate and structure of an idealized small‐scale outflow in the presence of surface waves using a fully coupled 3‐D hydrodynamic and spectral wave model. Wave‐current interactions significantly alter plume structure when compared to hydrodynamics‐only simulations. Wave dissipation injected into the water column as a flux of turbulent kinetic energy at the sea surface mixes the plume in the surf zone, while wave‐driven velocities reduce offshore plume propagation and enhance alongshore spreading. A series of simulations varying flow rate and offshore wave height indicate a log linear relationship between the surf zone volume‐integrated freshwater fraction and the ratio of wave to outflow momentum fluxes.